Sons & Lettres A pronunciation method for intermediate-level French - Walton, Stephen (Open textbook library., 2018)
Sons et lettres provides a set of classroom materials to train students to hear and produce the sounds of French and to recognize the regular spellings used to represent those sounds in print. The materials are inspired by a desire to help students feel more confident about their French pronunciation and more at home saying the many French words, familiar and unfamiliar, which they encounter in their studies, in French media and in their travels. In our experience, students are not given sufficient preparation to successfully decipher and pronounce French words. These materials are intended to fill that gap and to clear away the confusion that English speakers often feel when they see French words with seemingly mysterious combinations of letters.